Is Alice Needed by Any Flowers? Alice Is Needed by Flower Power! Musical Transformations of Alice in Wonderland by the Counterculture of the 60s - Koćma, Katarzyna (Porównania, 2016)
The paper presents musical development of Alice in Wonderland by Lewis Carroll from a perspective of the counterculture of the 60s. The authoress shows how the existence of psychodelia in arts and culture of that decade made Carroll’s work a kind of record of the so called “trip”. Trying to analyze what happens to the lyrics’ protagonists, for example Alice, Mad Hatter, Caterpillar or White Rabbit, the authoress indicates the transformations of them in songs of The Beatles, Jefferson Airplane, The Incredible String Band, The Monkees or Tom Northcott. The lyrics were divided into three parts: The Alice Who Knows, The Alice Who Is Gone and The Wonderland’s Inhabitants